Cardiac magnetic resonance imaging vs coronary angiography as primary strategy in newly diagnosed heart failure - Güder, Gülmisal; Reiter, Theresa; Bauer, Wolfgang R.; Papavassiliu, Theano; Schwab, Johannes; Pauschinger, Matthias; Lavall, Daniel; Wachter, Rolf; Berliner, Dominik; Bauersachs, Johann; Frantz, Stefan; Gelbrich, Götz; et al. (JACC Heart failure, 2025)
Background - New-onset heart failure with reduced ejection fraction (HFrEF) requires further diagnostic evaluation to determine its underlying cause. Despite the potential of cardiac magnetic resonance (CMR) imaging to identify ischemic and nonischemic causes, percutaneous invasive coronary angiography (CATH) remains the preferred tool for diagnosing ischemic cardiomyopathy (ICM). - Objectives - This study aimed to determine whether a CMR-first strategy could diagnose ICM as effectively as CATH (primary endpoint) and potentially reduce the number of invasive procedures (secondary endpoint). - Methods - In this multicenter 2-armed diagnostic trial (Magnetic Resonance Imaging vs Invasive Coronary Angiography as First-Line Diagnostic Modality in New-Onset Heart Failure), 229 adults with new-onset HFrEF were randomized to undergo CMR or CATH first and the other modality second. Separate expert panels evaluated both modalities, blinded to each other’s results. The cardiologist-in-charge was blinded to the panel results and served as the reference standard. - Results - A total of 203 patients (mean age: 62 ± 14 years, 28% women) had evaluable pairs of diagnostic modalities (108 CATH-first). For diagnosing ICM, the panels considered CATH to be sufficient in 100% (105/105) and CMR in 80% (76/95; P < 0.001). Compared with the reference, sensitivity for diagnosing ICM was high for both (CATH 91%, CMR 90%; P = 1.00), but CMR had lower specificity (98% vs 74%; P < 0.001). According to the CMR panel, 48% (46/95) of CATH procedures could have been avoided with a CMR-first strategy, dropping to 45% when excluding patients who underwent coronary interventions. - Conclusions - Although CATH was superior for diagnosing ICM, CMR showed similar sensitivity and could significantly reduce CATH procedures without increasing the risk of missing critical coronary interventions. Longitudinal studies are needed to assess whether a CMR-first strategy confers prognostic benefit. (Magnetic Resonance Imaging vs Invasive Coronary Angiography as First-Line Diagnostic Modality in New-Onset Heart Failure; ISRCTN16515058)
Online verfügbar: 12. Juli 2025, Artikeversion: 12. Juli 2025
Gesehen am 19.08.2025